Decisions at the end of life: the use and abuse of the concept of futility. - Pellegrino, Edmund D. (Medicina e Morale, 2002)
In this essay, I wish to suggest that the proper use of the term "futility" can be a useful bridge between the ethical formulation of ordinary and extraordinary and the decision in a particular case at the end of life. Futility in the clinical sense simply means that an illness or disease process has progressed to a point such that a proposed medical intervention can no longer serve the good of the patient. This paper is divided into three parts: 1) delineation of the concept of futility; 2) delineation of its abuses in particular clinical decisions; 3) definition of its proper use within the context of Roman Catholic anthropology and medical morality. Properly interpreted as a prudential guide within specific moral constraints, it can help to recover and explicate the continuing importance of the traditional terms ordinary and extraordinary, proportionate and disproportionate. These terms are central to the Roman Catholic Magisterium on end-oflife care, and they have strongly influenced subsequent Catholic approaches to end of life decisions.